Effect of tillage on the structural stability and resistance to penetration of a Inceptisol planted with arracacha (Arracacia xanthorrhiza Bancroft) in Boyaca - Pinto-Acero, Yomaira Liney; Álvarez-Herrera, Javier Giovanni; Forero-Ulloa, Fabio Emilio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
In the municipality of Boyaca (Boyaca, Colombia), arracacha production constitutes an important source of income for farmers. Because of the limited information on the technology used for this crop, the effect of different tillage systems (minimum tillage, conventional tillage and vertical tillage) on some of the main physical properties of a Typic Dystrudept was studied, with a slope of 3%, mountainous type landscape and hilly relief, using four sampling times (before preparation (E1), after preparation (E2), 100 days after planting (E3) and 180 days after planting (E4)). The design employed a randomized block, wherein each block corresponded to a type of farming and the treatments used two arracacha types (Yema de huevo and Paliverde). The lower values of penetration resistance were seen with the vertical tillage at 12.5, 17.5 and 20 cm with values of 262.8, 810.8 and 1337.5 kPa, respectively. Furthermore, the vertical tillage had a greater increased structural stability and larger percentage of aggregate distribution for sizes between 1 and 3 mm, with an average value of 31.4%, than the conventional tillage and minimum tillage, which had values of 22% and 25.2%, respectively, which favored root development in the arracacha plants. The biggest difference between the types of tillage in terms of aggregate size distribution was seen at 100 days after sowing. The evaluated arracacha materials did not significantly affect any of the evaluated soil parameters.